Global inequities in adverse pregnancy outcomes: what can we do? - James M. Roberts, MD; Seye Abimbola, MBChB, PhD; Tracy L. Bale, PhD; Aluisio Barros, MD, PhD; Zulfiqar A. Bhutta, MBBS, PhD; Joyce L. Browne, MD, PhD; Ann C. Celi, MD, MPH; Polite Dube, PhD; Cornelia R. Graves, MD; Marieke J. Hollestelle, PhD; Scarlett Hopkins, BSN, MA; Ali Khashan, PhD; et al. (Elsevier, 2024)
The Health Equity Leadership & Exchange Network states that "health equity exists when all people, regardless of race, sex, sexual orientation, disability, socioeconomic status, geographic location, or other societal constructs, have fair and just access, opportunity, and resources to achieve their highest potential for health." It is clear from the wide discrepancies in maternal and infant mortalities, by race, ethnicity, location, and social and economic status, that health equity has not been achieved in pregnancy care. Although the most obvious evidence of inequities is in low-resource settings, inequities also exist in high-resource settings. In this presentation, based on the Global Pregnancy Collaboration Workshop, which addressed this issue, the bases for the differences in outcomes were explored. Several different settings in which inequities exist in high- and low-resource settings were reviewed. Apparent causes include social drivers of health, such as low income, inadequate housing, suboptimal access to clean water, structural racism, and growing maternal healthcare deserts globally. In addition, a question is asked whether maternal health inequities will extend to and be partially due to current research practices. Our overview of inequities provides approaches to resolve these inequities, which are relevant to low- and high-resource settings. Based on the evidence, recommendations have been provided to increase health equity in pregnancy care. Unfortunately, some of these inequities are more amenable to resolution than others. Therefore, continued attention to these inequities and innovative thinking and research to seek solutions to these inequities are encouraged.